Identifying the psychosocial aspects of crowd during pilgrimage: the experiences of a group of Pakistani female hajj pilgrims - Abdul Rahman, Shukran; Sulong, Jasni; Mat Saad, Zarina; Mohd Mahudin, Nor Diana; Ahmad Hatta, Zulkarnain; Mohd Hashim, Intan Hashimah; Abdul Ghani, Noraida (2019)
Hajj is a series of activities which involve the presence of many people of diverse backgrounds in specific sites. It is an annual event which necessitates Muslims from all over the world to travel to Makkah during the Hajj season. The participation in hajj involves a number of remarkable experiences by the pilgrims who encounter various new incidents that involve their physical, psychosocial and social experiences. Despite the widely reported accounts of hajj, less has been conducted to study the experience of people who travel from different parts of the world to Makkah. The objective of this paper is to report the findings from a focus group discussion which examined the experiences of hajj among Pakistani female pilgrims. Data was collected from 11 respondents from Lahore, Pakistan. They were required to state their confrontations in hajj sites; and the reasons for having such experiences. They reported both positive and negative feelings during hajj; highlighted their and others’ pattern of behaviours when performing hajj including commendable and hazardous actions that they observed among pilgrims and hajj service providers. They also reported their concerns over crowd management issues, and the pilgrims’ lack of mental preparation to be with others of different cultural backgrounds. The findings serve as a basis for the development of interventions to help hajj managers, policy makers, and future hajj pilgrims to understand the psychological states and sociological conditions during hajj.